Defining a standard set of patient-centred outcomes for lung cancer. Issue 3 (7th July 2016) - Mak, Kimberley S.; van Bommel, Annelotte C.M.; Stowell, Caleb; Abrahm, Janet L.; Baker, Matthew; Baldotto, Clarissa S.; Baldwin, David R.; Borthwick, Diana; Carbone, David P.; Chen, Aileen B.; Fox, Jesme; Haswell, Tom; et al.
In lung cancer, outcome measurement has been mostly limited to survival. Proper assessment of the value of lung cancer treatments, and the performance of institutions delivering care, requires more comprehensive measurement of standardised outcomes. The International Consortium for Health Outcomes Measurement convened an international, multidisciplinary working group of patient representatives, medical oncologists, surgeons, radiation oncologists, pulmonologists, palliative care specialists, registry experts and specialist nurses to review existing data and practices. Using a modified Delphi method, the group developed a consensus recommendation ("the set") on the outcomes most essential to track for patients with lung cancer, along with baseline demographic, clinical and tumour characteristics (case-mix variables) for risk adjustment. The set applies to patients diagnosed with nonsmall cell lung cancer and small cell lung cancer. Our working group recommends the collection of the following outcomes: survival, complications during or within 6 months of treatment and patient-reported domains of health-related quality of life including pain, fatigue, cough and dyspnoea. Case-mix variables were defined to improve interpretation of comparisons. We defined an international consensus recommendation of the most important outcomes for lung cancer patients, along with relevant case-mix variables, and are working to support adoption and reporting of these measures globally. #ICHOM Lung Cancer Standard Set of patient-centred outcomes: aligning global efforts to improve lung cancer care http://ow.ly/bFDR300EhY7